2011
DOI: 10.1074/jbc.m111.260562
|View full text |Cite
|
Sign up to set email alerts
|

Rho Signaling Regulates Pannexin 1-mediated ATP Release from Airway Epithelia

Abstract: ATP released from airway epithelial cells promotes purinergic receptor-regulated mucociliary clearance activities necessary for innate lung defense. Cell swelling-induced membrane stretch/strain is a common stimulus that promotes airway epithelial ATP release, but the mechanisms transducing cell swelling into ATP release are incompletely understood. Using knockdown and knockout approaches, we tested the hypothesis that pannexin 1 mediates ATP release from hypotonically swollen airway epithelia and investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
212
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(229 citation statements)
references
References 74 publications
13
212
2
Order By: Relevance
“…In other cases of ball-and-chain inhibition, there has been no physiological mechanism described for cutting the chain to permanently remove channel inhibition, as we have found for caspase-mediated cleavage and activation of hPANX1. Although this cleavage-based mechanism seems appropriate for a terminal process such as apoptosis, we expect that more subtle mechanisms will account for other forms of PANX1 activation associated with different physiological conditions (10,26,27). Nevertheless, because C-terminal inhibition in the intact channel depends on its association with the pore, our data suggest that these other PANX1 activation mechanisms will also require some disruption of the C terminus from its inhibitory interaction site within the channel pore.…”
Section: Discussionmentioning
confidence: 78%
“…In other cases of ball-and-chain inhibition, there has been no physiological mechanism described for cutting the chain to permanently remove channel inhibition, as we have found for caspase-mediated cleavage and activation of hPANX1. Although this cleavage-based mechanism seems appropriate for a terminal process such as apoptosis, we expect that more subtle mechanisms will account for other forms of PANX1 activation associated with different physiological conditions (10,26,27). Nevertheless, because C-terminal inhibition in the intact channel depends on its association with the pore, our data suggest that these other PANX1 activation mechanisms will also require some disruption of the C terminus from its inhibitory interaction site within the channel pore.…”
Section: Discussionmentioning
confidence: 78%
“…15,16,35,52 Surprisingly, the overall viability and health of Panx1 null mice is relatively unaltered, which seems counterintuitive when we consider the ubiquitous expression of Panx1 in mouse organs and tissues. These findings raise three essential questions: is Panx1 not that important after all?…”
Section: Pannexin Compensation As Revealed By Mutant Micementioning
confidence: 90%
“…Some options include preadsorption with cognate peptides as shown in Figures 6 and 7, or the use of tissues and cells from Panx null mouse models as has been reported for the Panx1 CT-395 antibody. 15,35 Although Panx3 was found within intracellular compartments in rat cochlear bone, 46 it was also found at the cell surface and within intracellular compartments in murine chondrocytes and chondrogenic cell lines (ATDC5). 21 Panx2, on the other hand, has been localized primarily to intracellular compartments 9,38,39 and displays only limited cell surface distribution that is increased when coexpressed with Panx1.…”
Section: Diverse Localization Profiles Of Pannexinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These new peptides have shed light on the gating of Cx43 hemichannels which appears to be tightly regulated by interactions between the intracellular domains of Cx43. Due to the increasing success of mimetic peptides in targeting Cx hemichannels, a mimetic peptide of the first extracellular loop of Panx1 termed 10 panx1 was developed and has subsequently been shown to significantly inhibits channel currents, dye uptake and ATP release mediated by Panx1 in a number of cell types [164,196,197]. The Panx mimetic peptide has not escaped the issue of cross-inhibition, however, as it was recently shown that the 10 panx1 peptide also blocks Cx46 hemichannel currents [193].…”
mentioning
confidence: 99%